2015
DOI: 10.1515/nuka-2015-0084
|View full text |Cite
|
Sign up to set email alerts
|

The acid-catalyzed interaction of melanin with nitrite ions. An EPR investigation

Abstract: The interaction of synthetic dihydroxyphenylalanine (DOPA) melanin (DM) with nitrite ions, NO2−, in the pH 3.6–7.0 range, has been investigated using electron paramagnetic resonance (EPR). We found that especially at pH <5.5 (from ca. 5.5 to 3.6) the reaction of DM with nitrite generated large quantities of new melanin radicals, which implies the involvement of nitrous acid, HNO2, in the radical formation process. Measurements carried out at constant pH of 3.6 showed that the melanin signal increased togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Melanin production seems to be induced in the presence of a moderate concentration of RNS in the environment. A potential mechanism that mediates this response can be found in an in vitro study conducted by Matuszak and colleagues where they reported that the concentration of synthetic DOPA-melanin pigments in an acidic buffer increased four-fold in the presence of 0.5 mM NaNO 2 whereas the presence of H 2 O 2 in the medium did not produce the same effect 32 . They proposed that the interaction of DOPA-melanin with nitrite at acidic pH leads to melanin oxidation, followed by the generation of a large number of melanin radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Melanin production seems to be induced in the presence of a moderate concentration of RNS in the environment. A potential mechanism that mediates this response can be found in an in vitro study conducted by Matuszak and colleagues where they reported that the concentration of synthetic DOPA-melanin pigments in an acidic buffer increased four-fold in the presence of 0.5 mM NaNO 2 whereas the presence of H 2 O 2 in the medium did not produce the same effect 32 . They proposed that the interaction of DOPA-melanin with nitrite at acidic pH leads to melanin oxidation, followed by the generation of a large number of melanin radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Melanoma [89] and its metastases [90,91] often (more often than carcinomas, however less often than leukemias) undergo spontaneous regression [92,93] with the involvement of immune mechanisms [94][95][96][97][98][99], in which hemorrhagic necrosis has been found to be typically responsible for this regression [94][95][96][97][98][99]. Even the primary tumors which were the source of transplantable lines of Cloudman S91 [100,101] and B16 melanoma [102,103] were described as hemorrhagic.…”
Section: Discussionmentioning
confidence: 99%